Influencia de los estilos de crianza y conductas disruptivas en la comprensión lectora de estudiantes del sexto grado de las instituciones educativas públicas primarias del distrito de Iquitos 2022 - Calderón Vásquez, Libny de Fátima (2024)
The purpose of this study was to explain the influence of parenting styles and disruptive behaviors on the reading comprehension of sixth grade students in public elementary schools in the urban area of the district of Iquitos 2022. The research work is of a non-experimental explanatory level and multiple correlational design. The population consisted of 630 elementary school students, and the sample consisted of 239 students, chosen by the stratified sampling method by proportional allocation. The ESPA 29 survey technique was applied for Parenting Styles and ESPIRI for Disruptive Behavior, and the Reading Comprehension test. The questionnaire of questions for the three variables was used as an instrument. The following were the most relevant conclusions: There is a direct and significant influence of parenting styles and disruptive behaviors on the sixth-grade students' reading comprehension at the primary public schools located in the city's Iquitos district in 2022. Significant results were found using the Chi-square statistical test, allowing us to accept the study's hypothesis.